Contextualizing English Language Teaching for Technology Undergraduates in Sri Lanka: A Need-based Approach to Localization - Boby Anestine, A. (University of Jaffna, 2025)
In Sri Lanka, English is an important foreign language for further learning and professional development. Technology undergraduates require proficiency in English to engage with global research and participate in technical discourse. Many English language teachers lack the necessary digital literacy and familiarity with the technological domain. This leads to mismatch between what is taught and what students actually need. This becomes a problem when they teach to the students who are learning technology field. The lessons are often based on general topics and do not include the specific tasks that technology students need to know. This study proposes a needs-based approach to make English language teaching more relevant, contextualized and effective for Sri Lankan technology undergraduates. It focuses on finding out what both students and teachers need. The research includes students’ surveys, classroom observations and interviews with teachers to understand the main problem in teaching English for technology students. It also looks at how local languages (Tamil and Sinhala) can support learning and how technology and real-world content can be included in lessons. This study uses a mixed method approach to explore the needs of both students and teachers in teaching and learning English Language. It involved 120 undergraduate students from faculty of technology, University of Jaffna. The study aims to show that the students can improve their understanding and ability to use the English for their real time situation when English language teaching is made more relevant and localized to the students’ field. The study explains that current English teaching methods are not fully meeting the needs of technology undergraduates, teachers require more support in using technology and understanding technical language. It also suggests new ways to train teachers and use better teaching methods to prepare students for both their studies and their future jobs in the technology sector. A localized needs-based approach can make English Language teaching more relevant and effective.
Keywords: Contextualized English Language Teaching (ELT); Need-based language instruction; Technology undergraduates; Localizing; Familiarity; Technology knowledge